Immunoreactivity of Sera From Low to Moderate Malaria-Endemic Areas Against Plasmodium vivax rPvs48/45 Proteins Produced in Escherichia coli and Chinese Hamster Ovary Systems - Arévalo-Herrera, Myriam; Miura, Kazutoyo; Cespedes, Nora; Echeverry, Carlos; Solano, Eduardo; Castellanos, Angélica; Ramirez, Juan Sebastián; Miranda, Adolfo; Kajava, Andrey V.; Long, Carole; Corradin, Giampietro; Herrera, Sócrates (Frontiers in Immunology, 2021)
P48/45 are conserved gametocyte antigens involved in Plasmodium parasite fertilization. A recombinant Plasmodium vivax P48/45 (rPvs48/45) protein expressed in Escherichia coli (E. coli) was highly antigenic and immunogenic in experimental animals and elicited specific transmission-blocking (TB) antibodies in a previous pilot study. Here, a similar Pvs48/45 gene was expressed in Chinese Hamster Ovary (CHO) cells and we compared its immunoreactivity with the E. coli product. Specific antibody titers were determined using plasma from Colombian individuals (n=227) living in endemic areas where both P. vivax and P. falciparum are prevalent and from Guatemala (n=54) where P. vivax is highly prevalent. In Colombia, plasma seroprevalence to CHO-rPvs48/45 protein was 46.3%, while for E. coli-rPvs48/45 protein was 36.1% (p<0.001). In Guatemala, the sero prevalence were 24.1% and 14.8 % (p<0.001), respectively. Reactivity index (RI) against both proteins showed an age-dependent increase. IgG2 was the predominant subclass and the antibody avidity index evaluated by ELISA ranged between 4-6 mol/L. Ex vivo P. vivax mosquito direct membrane feeding assays (DMFA) performed in presence of studied plasmas, displayed significant parasite transmission-blocking (TB), however, there was no direct correlation between antibody titers and oocysts transmission reduction activity (%TRA). Nevertheless, DMFA with CHO rPvs48/45 affinity purified IgG showed a dose response; 90.2% TRA at 100 μg/mL and 71.8% inhibition at 10 μg/mL. In conclusion, the CHO-rPvs48/45 protein was more immunoreactive in most of the malaria endemic places studied, and CHO-rPvs48/45 specific IgG showed functional activity, supporting further testing of the protein vaccine potential.